2019
DOI: 10.1007/s42488-019-00010-1
|View full text |Cite
|
Sign up to set email alerts
|

Panacea of challenges in real-world application of big data analytics in healthcare sector

Abstract: Big data analytics is emerging ever since it has been introduced in the healthcare sector. It has given tools to gather, operate, assess, and associate large volumes of disparate, structured and unstructured data that are generated by present healthcare systems. Big data has been lately functional towards helping in the process of care delivery and disease exploration. Howbeit, due to some fundamental problems, the progress in care delivery and disease exploration is blocked. Fundamental problems such as data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…In any case, Cabero-Almenara stated that it was necessary. preparation and financial speculation to guarantee its accomplishment in the study hall [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, Cabero-Almenara stated that it was necessary. preparation and financial speculation to guarantee its accomplishment in the study hall [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gather information pictures through the TOF camera on the endoscope, and show a visual connection point to the clinical staff [5]. Deng et al recommended that the overall comprehension of increased reality in present day times has changed, underscoring the two signs of three-layered and intelligent, and adequately recognized plane postproduction innovation and film and TV bundling innovation and expanded reality innovation [6]. Gogolin and Gogolin suggested that expanded reality can advance the trading of involvement with increased reality innovation and, simultaneously, give directing assessments to deciding future examination fields and future improvement patterns [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances in technology in contemporary times have made many things possible such as creating virtual worlds or enhancing existing real-world objects and scenarios through multiple sensory modes [1]. Augmented reality (AR) and virtual reality (VR) have the capability to alter the way entertainment, shopping, health activities, recreation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural sector accounts for 18 percent of GDP in India and provides 50 percent of the country's population with jobs. Progress in the agricultural sector would fuel rural development, contributing further to rural transformation and ultimately to systemic change [3,4].…”
Section: Introductionmentioning
confidence: 99%